Signaling Pathways Regulating Thermogenesis - Tabuchi, Chihiro; Sul, Hei Sook (Frontiers in Endocrinology, 2021)
Obesity, an excess accumulation of white adipose tissue (WAT), has become a global epidemic and is associated with complex diseases, such as type 2 diabetes and cardiovascular diseases. Presently, there are no safe and effective therapeutic agents to treat obesity. In contrast to white adipocytes that store energy as triglycerides in unilocular lipid droplet, brown and brown-like or beige adipocytes utilize fatty acids (FAs) and glucose at a high rate mainly by uncoupling protein 1 (UCP1) action to uncouple mitochondrial proton gradient from ATP synthesis, dissipating energy as heat. Recent studies on the presence of brown or brown-like adipocytes in adult humans have revealed their potential as therapeutic targets in combating obesity. Classically, the main signaling pathway known to activate thermogenesis in adipocytes is β3-adrenergic signaling, which is activated by norepinephrine in response to cold, leading to activation of the thermogenic program and browning. In addition to the β3-adrenergic signaling, numerous other hormones and secreted factors have been reported to affect thermogenesis. In this review, we discuss several major pathways, β3-adrenergic, insulin/IGF1, thyroid hormone and TGFβ family, which regulate thermogenesis and browning of WAT.